An Error Analysis of Using Present Tense in Writing Daily Activities at the 7 th Year Students of SMP DINIYAH AL-FALAHIYAH LAMONGAN - Sailatun Nabilah (Journal of Research in Foreign Language Teaching (JRFLT), 2018)
This research aimed to find out the types of grammatical error. This research used Qualitative method. The subjects of this research was the seventh year students, class A at SMP Diniyah Al-falahiyah Gowa Pomahanjanggan Turi Lamongan. This research took only ten students to be the participant which is suggested from the teacher. They were categorized as high enthusiasm in English subject. Students? writings about their daily activities were as the data of this research. The students? error categorizedinto four types based on Dulay, Burt, and Krashen in Ellis (2008) such Error Omission, Error Addition, Error misformation and Error misordering. But,the result of the study showed that there were three types of error made by students; omission, addition, miss formation. The errors related to omission were 5 errors. While the errors related to Addition were 7 errors. And the errors related to misformation were 2 errors.